Application of an electrocardiography device (iECG) for heart rhythm analysis after exercise in Thoroughbred horses. Issue 3 (2nd December 2021) - Nath, LC; Forbes, G; Elliott, AD; Tomren, V; Ryan, A; Franklin, SH
Abstract : AliveCor is a smartphone electrocardiography device (iECG) providing automated heart rate (HR) and rhythm determination. Atrial fibrillation (AF) in horses often is paroxysmal and rapid ECG acquisition is needed for diagnostic confirmation. iECGs were collected post‐race from 15 horses with AF and 64 horses in sinus rhythm (SR). Results of manual assessment were compared to 3 commercial algorithms for HR and rhythm. Agreement between manually derived HR (HRM ) and HR derived by the AliveECG Vet (HRVET ) and Kardia version‐1 (KV1 HR) and Kardia advanced (KADV HR) algorithms was quantified by the Bland–Altman limits of agreement test. Agreement between manual rhythm classification and KV1 and KADV algorithms for AF and SR was calculated by the Kappa statistical coefficient. The agreement (bias, 95% limits), between HRM and HRVET was 7.1 BPM (−29 to 43) in AF and −4.2 BPM (−38 to 30) in SR, between HRM and KV1 HR, was −0.3 BPM (−31 to 30) in AF and 0.2 BPM (−3 to 4) in SR, and between HRM and KADV HR was 7.0 BPM (−29 to 43) in AF and 0.2 BPM (−3.9 to 4.2) in SR. Agreement between manual rhythm classification and KV1 was 0.36 (0.13–0.59), and KADV was 0.84 (0.68–0.99). Sensitivity and specificity for identification of AF and SR of the KV1 algorithm were 60, 100% and 83, 100%, respectively, and of KADV was 87, 100% and 93, 100% respectively. The Kardia algorithms improved precision for HR determination in SR but not AF. The advanced algorithm accurately distinguished between AF and SR. The iECG is suitable for recording episodes of AF following exercise.